Remission for Terrorist Convicts: Challenges and Solutions to the Indonesian Law - Najemi, Andi; Rapik, Mohamad; Rosmidah, Rosmidah (Jambe Law Journal, 2022)
This article aims at discussing remission granted upon terrorsime convicts. It has been debated among academics as to whether giving remision or reduction of sentence upon the pepertrator of an extra ordinary crime is a wise policy or not. Some of them argue that Indoensia is a country based on law. Any policy, therefore, shall refer to laws which allow remision for any prisoners who have met certain conditions including terrorism convicts. Other academics, however, insist on argument that providing remission to terrorism conficts is nothing but to let to destroy the country for they (the terrorists) might hold radical views which are not recovered with imprisonment. In this article, the authors argue that the laws are still the main reference as long as the legal perspective is concerned. However, as the laws have not provided special regulation for granting remission upon terrrorism convicts, this article proposed to ammend or revisit the laws related to such issue. The revision or ammendmet is urgent in order to provide wiser regulation as long remission upon terrorism convicts is concerned